Triple heat treatment method for synergistically improving strength and plasticity of Ti80 titanium alloy

Through the triple methods of near-β heat treatment, two-phase zone heat treatment and aging heat treatment, a multi-morphology and multi-scale alpha phase structure is formed, which solves the problem of difficulty in taking into account the strength and plasticity of the existing Ti80 titanium alloy, and significantly improves the overall performance of the material .

CN119287294APending Publication Date: 2025-01-10NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411497727.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing Ti80 titanium alloy heat treatment process is difficult to maintain sufficient plasticity while increasing the strength, and the existing structure cannot meet the comprehensive performance requirements of marine engineering equipment.

Method used

Using the triple heat treatment method of near-β heat treatment, two-phase zone heat treatment and aging heat treatment, the multi-morphological and multi-scale structure of the isometric α phase, sheet α phase and needle-shaped α phase are formed by controlling the insulation temperature, time and cooling method. .

Benefits of technology

The synergistic improvement of the strength and plasticity of Ti80 titanium alloy is achieved, and the microstructure formed is an equiaxed α phase (8~12%) + a sheeted α phase (30~35%) + a needle-shaped α phase, which improves the integration of the material Mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287294A_ABST
    Figure CN119287294A_ABST
Patent Text Reader

Abstract

The invention discloses a triple heat treatment method for synergistically improving the strength and plasticity of a Ti80 titanium alloy, which comprises the following steps: 1, near beta heat treatment: carrying out heat preservation on the Ti80 titanium alloy at 985-990 DEG C for 30-60 minutes, and carrying out water quenching to room temperature; the second step of two-phase region heat treatment, specifically, the Ti80 titanium alloy subjected to near-beta heat treatment is subjected to heat preservation at the temperature of 955-965 DEG C for 60-120 min, and water quenching is conducted to the room temperature; and in the third step of aging heat treatment, the Ti80 titanium alloy subjected to two-phase region heat treatment is subjected to heat preservation at 500-550 DEG C, the heat preservation time is 60-120 min, and the Ti80 titanium alloy is air-cooled to the room temperature. By controlling the heat preservation temperature, the heat preservation time and the cooling mode of the triple heat treatment process, a multi-morphology and multi-scale microstructure of an equiaxed alpha phase (8-12%), a lamellar alpha phase (30-35%) and a needle-shaped alpha phase is formed in the Ti80 titanium alloy, the average thickness of the lamellar alpha phase is smaller than 1.5 micrometers, the average thickness of the needle-shaped alpha phase is smaller than 120 nm, and therefore the strength and plasticity of the Ti80 titanium alloy are cooperatively improved. The application range of the Ti80 titanium alloy in the marine industrial field can be widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium alloy heat treatment, and specifically relates to a triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy. Background Art

[0002] With the rapid development of my country's marine engineering field, the comprehensive performance requirements for marine engineering equipment such as manned submersibles, offshore oil drilling platforms, polar research vessels, etc. are constantly increasing. Ti80 titanium alloy is a near-α titanium alloy with excellent comprehensive performance. The alloy has the characteristics of high specific strength, good corrosion resistance, and excellent welding performance. It has been widely used in pump bodies, valve bodies, pressure vessels, submersible pressure hulls and other stress-bearing structural parts in chemical corrosive environments.

[0003] The microstructure of titanium alloy determines its mechanical properties, and thus its service performance. Titanium alloy can form four basic organizational forms through hot working or heat treatment: equiaxed organization, dual-state organization, basket organization, and lamellar organization. Each of them has its own advantages and disadvantages in terms of strength, plasticity, fracture toughness, fatigue performance, etc. The three-state organization has multiple organizational characteristics, forming a structure of equiaxed α phase + lamellar α phase + β transformation organization, and has better comprehensive mechanical properties; At present, Ti80 titanium alloy is mainly formed by heat treatment or thermomechanical processing to form equiaxed organization or dual-state organization, and its strength level cannot meet the service requirements, and while improving the strength, it sacrifices plasticity to a certain extent. Therefore, it is necessary to further optimize the heat treatment process in order to construct a better performance organizational form in Ti80 titanium alloy. Summary of the invention

[0004] In view of the shortcomings of the above-mentioned prior art, the present invention obtains a multi-morphology and multi-scale α phase organizational morphology with equiaxed α phase (8-12%) + lamellar α phase (30-35%) + needle-shaped α phase through near-β heat treatment, two-phase zone heat treatment and aging heat treatment, thereby synergistically improving the strength and plasticity level of Ti80 titanium alloy.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides a triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy, which specifically comprises the following steps: Step 1: Near-β heat treatment: keep the Ti80 titanium alloy at 985-990°C for 30-60 minutes, and quench with water to room temperature; Step 2, two-phase region heat treatment: the Ti80 titanium alloy after the near-β heat treatment is kept at 955-965° C. for 60-120 min, and water quenched to room temperature; Step 3: Aging heat treatment: The Ti80 titanium alloy after the two-phase zone heat treatment described in step 2 is kept at 500-550° C. for 60-120 min, and then air-cooled to room temperature.

[0006] Furthermore, after the near-β heat treatment and water quenching in step 1, the microstructure of the Ti80 titanium alloy is equiaxed α phase + ɑ′ phase, wherein the content of the equiaxed α phase is 4-6%, and the average size of the equiaxed α phase is 6.5-7.5 μm.

[0007] Furthermore, after the two-phase zone heat treatment and water quenching in step 2, the microstructure of the Ti80 titanium alloy is equiaxed α phase + lamellar α phase + ɑ′ phase, wherein the equiaxed α phase content is 8-12%, the average size of the equiaxed α phase is 7.5-8.5 μm, the lamellar α phase content is 25-30%, and the average thickness of the lamellar α phase is less than 1.3 μm.

[0008] Furthermore, after the aging heat treatment and air cooling in step 3, the microstructure of the Ti80 titanium alloy is equiaxed α phase + lamellar α phase + β transformation structure, wherein the equiaxed α phase content is 8-12%, the lamellar α phase content is 30-35%, the average thickness of the lamellar α phase is less than 1.5 μm, and a needle-shaped α phase with an average thickness of less than 120 nm is precipitated in the β transformation structure.

[0009] Furthermore, in the water quenching process in step 1 and step 2, the quenching transfer time is 3 to 5 seconds, and the quenching temperature is 10 to 25°C.

[0010] Furthermore, the heat treatment is carried out in a resistance furnace in a vacuum or argon atmosphere, and during the heat treatment process, the Ti80 titanium alloy is placed in the middle of the furnace of the resistance furnace.

[0011] Furthermore, the heating method of the heat treatment is to heat the sample to the desired temperature.

[0012] Furthermore, the Ti80 titanium alloy needs to be cleaned and degreased before heat treatment and wrapped with titanium foil, and the oxide scale on the surface needs to be removed after heat treatment.

[0013] Furthermore, the constituent elements of the Ti80 titanium alloy are Al: 5.5-6.1wt%, Zr: 2.1-2.5wt%, Nb: 2.5-3.5wt%, Mo: 0.8-1.2wt%, and the rest are Ti and inevitable impurities, and the inevitable impurity elements include Si, C, N, H, O, and Fe, among which the Fe content is less than 0.05wt%.

[0014] The present invention also provides a Ti80 titanium alloy obtained by the above-mentioned triple heat treatment method, wherein the microstructure of the Ti80 titanium alloy is equiaxed α phase + lamellar α phase + β transformation structure; the equiaxed α phase content is 8-12%, the lamellar α phase content is 30-35%, the lamellar α phase has an average thickness of less than 1.5 μm, and a needle-shaped α phase with an average thickness of less than 120 nm is precipitated in the β transformation structure.

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The cooling method of the near-β heat treatment of the present invention is water cooling to form a microstructure of equiaxed α phase + ɑ′ phase. The ɑ′ phase will serve as a nucleation site for the lamellar α phase during the two-phase region heat treatment to form a lamellar α phase with a desired content and size. If a furnace cooling or air cooling cooling method is selected, the lamellar α phase content will be reduced and the size will be greatly increased, thereby reducing the strength and plasticity of the Ti80 titanium alloy.

[0016] The cooling method of the two-phase zone heat treatment of the present invention is water cooling to form a microstructure of equiaxed α phase + lamellar α phase + ɑ′ phase. The ɑ′ phase will further serve as a nucleation site for the needle-like α phase during the aging heat treatment to form a needle-like α phase of a desired size. If a furnace cooling or air cooling cooling method is selected, the content and size of the lamellar α phase will increase and the needle-like α phase may not precipitate during the subsequent aging heat treatment process, thereby reducing the strength and plasticity of the Ti80 titanium alloy.

[0017] The present invention adopts a triple heat treatment method of near-β heat treatment water cooling + two-phase zone heat treatment water cooling + aging heat treatment air cooling, controls the holding temperature, holding time and cooling method of the triple heat treatment, regulates the tissue evolution process, and obtains a multi-morphology and multi-scale microstructure with equiaxed α phase (8-12%) + lamellar α phase (30-35%) + needle-shaped α phase, the average thickness of the lamellar α phase is less than 1.5μm, and the average thickness of the needle-shaped α phase is less than 120nm, thereby achieving a synergistic improvement in the strength and plasticity of the Ti80 titanium alloy.

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings of the embodiments will be briefly described below. It should be noted that the drawings described below only relate to some embodiments of the present disclosure, but are not intended to limit the present disclosure, wherein: Figure 1 This is a low-magnification microstructure image of the Ti80 titanium alloy after triple heat treatment provided in Example 1 of the present invention.

[0019] Figure 2 This is a high-magnification microstructure image of the Ti80 titanium alloy after triple heat treatment provided in Example 2 of the present invention.

[0020] Figure 3 This is a microstructure diagram of the Ti80 titanium alloy after triple heat treatment provided in Comparative Example 1 of the present invention.

[0021] Figure 4 This is a microstructure diagram of the Ti80 titanium alloy after double heat treatment provided in Comparative Example 2 of the present invention.

[0022] Figure 5 This is a microstructure diagram of the Ti80 titanium alloy after triple heat treatment provided in Comparative Example 3 of the present invention.

[0023] Figure 6 It is a room temperature engineering stress-engineering strain curve diagram of the Ti80 titanium alloy provided in Examples 1-2 of the present invention and Comparative Examples 1-3.

[0024] Figure 7 This is a low-magnification microstructure diagram of the Ti80 titanium alloy before triple heat treatment provided by the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution of the embodiments of the present disclosure will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by those skilled in the art without creative work also fall within the scope of protection of the present disclosure.

[0026] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which the subject matter of the present disclosure belongs. It will be further understood that terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the specification and the relevant art, and will not be interpreted in an idealized or overly formal form unless otherwise explicitly defined herein.

[0027] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiments" in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0028] The present invention provides a triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy, which specifically comprises the following steps: Step 1, near-β heat treatment: the Ti80 titanium alloy is preferably kept at 985-990°C, for example, 985°C, 987°C, 990°C; the holding time is preferably 30-60min, for example, 30min, 35min, 45min, 50min, 55min, 60min, and then water quenched to room temperature; Step 2, two-phase region heat treatment: the Ti80 titanium alloy after the near-β heat treatment is preferably kept at 955-965°C, for example, 955°C, 960°C, 965°C, and the holding time is preferably 60-120min, for example, 60min, 75min, 85min, 95min, 100min, 110min, 120min, and water quenched to room temperature; Step 3, aging heat treatment: The Ti80 titanium alloy after the two-phase zone heat treatment in step 2 is preferably kept at 500-550°C, for example, 500°C, 525°C, 530°C, 540°C, 550°C, and the holding time is preferably 60-120min, which can be 60min, 75min, 85min, 95min, 100min, 110min, 120min, and air-cooled to room temperature.

[0029] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, wherein the constituent elements of the Ti80 titanium alloy used in the embodiment are Al: 5.94wt%, Zr: 2.33wt%, Nb: 3.01wt%, Mo: 1.03wt%, Si: 0.04wt%, C: 0.012wt%, N: 0.028wt%, H < 0.0006wt%, O: 0.061wt%, Fe < 0.05wt% by mass percentage. The initial microstructure of the Ti80 is equiaxed α phase (59.6%) + secondary α phase (34.3%) + β phase (6.1%), without lamellar α phase structure, wherein the equiaxed α phase size is about 17.1μm, and the secondary α phase thickness is about 1μm. Example 1

[0030] A triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy is provided, comprising the following steps: Step 1, near-β heat treatment: heat the tube furnace to 990°C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, place the Ti80 titanium alloy wrapped with titanium foil in the middle of the furnace, ensure that the heating temperature is accurate and the heating is uniform, and after 35 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and quench it in water. The quenching transfer time is 3~5s, and the quenching water temperature is 10~25°C.

[0031] Step 2, two-phase zone heat treatment: heat the tube furnace to 960 ° C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, wrap the Ti80 titanium alloy after near-β heat treatment with titanium foil and place it in the middle of the furnace to ensure accurate heating temperature and uniform heating. After 60 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and quench it in water. The quenching transfer time is 3~5s, and the quenching water temperature is 10~25 ° C.

[0032] Step 3, aging heat treatment: heat the tube furnace to 550 ° C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, wrap the Ti80 titanium alloy after two-phase zone heat treatment with titanium foil and place it in the middle of the furnace to ensure that the heating temperature is accurate and the heating is uniform. After 60 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and cool it in the air.

[0033] Figure 1 This is a low-magnification microstructure diagram of the Ti80 titanium alloy after triple heat treatment in Example 1 of the present invention. The diagram shows that Ti80 presents multi-morphology and multi-scale α phase after triple heat treatment, and the organizational parameters are equiaxed α phase (9.5%) + lamellar α phase (33.6%) + β transformation organization, and the average thickness of the lamellar α phase is less than 1.5μm. Figure 2 This is a high-magnification microstructure diagram of the Ti80 titanium alloy after triple heat treatment in Example 1 of the present invention. The diagram shows that nanometer-scale needle-shaped α phase is precipitated in the β-transformed structure, which is criss-crossed and distributed with an average thickness of about 120 nm.

[0034] In this embodiment, the room temperature tensile mechanical properties of the Ti80 titanium alloy after the above triple heat treatment are as follows: yield strength is 870 MPa, tensile strength is 991 MPa, and total elongation at break is 19.3%. Example 2

[0035] A triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy is provided, comprising the following steps: Step 1, near-β heat treatment: heat the tube furnace to 985°C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, place the Ti80 titanium alloy wrapped with titanium foil in the middle of the furnace to ensure accurate heating temperature and uniform heating. After 45 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and quench it in water. The quenching transfer time is 3-5s, and the quenching water temperature is 10-25°C.

[0036] Step 2, two-phase zone heat treatment: heat the tube furnace to 955 ° C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, rewrap the Ti80 titanium alloy after near-β heat treatment with titanium foil and place it in the middle of the furnace to ensure accurate heating temperature and uniform heating. After 75 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and quench it in water. The quenching transfer time is 3~5s, and the quenching water temperature is 10~25 ° C.

[0037] Step 3, aging heat treatment: heat the tube furnace to 500°C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, rewrap the Ti80 titanium alloy after two-phase zone heat treatment with titanium foil and place it in the middle of the furnace to ensure that the heating temperature is accurate and the heating is uniform. After 90 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and cool it in the air; In this embodiment, the microstructure parameters of the Ti80 titanium alloy after the above triple heat treatment are equiaxed α phase (11.2%) + lamellar α phase (32.1%) + β transformation structure, the average thickness of the lamellar α phase is less than 1.4 μm, and a needle-shaped α phase with an average thickness of about 110 nm is precipitated in the β transformation structure.

[0038] In this embodiment, the room temperature tensile mechanical properties of the Ti80 titanium alloy after the above triple heat treatment are as follows: yield strength is 864 MPa, tensile strength is 1005 MPa, and total elongation at break is 21.4%.

[0039] Comparative Example 1 Step 1, near-β heat treatment: heat the tube furnace to 990°C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, place the Ti80 titanium alloy wrapped with titanium foil in the middle of the furnace, ensure that the heating temperature is accurate and the heating is uniform, and after 35 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and quench it in water. The quenching transfer time is 3~5s, and the quenching water temperature is 10~25°C.

[0040] Step 2, two-phase zone heat treatment: heat the tube furnace to 960 ° C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, rewrap the Ti80 titanium alloy after near-β heat treatment with titanium foil and place it in the middle of the furnace to ensure accurate heating temperature and uniform heating. After 60 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and quench it in water. The quenching transfer time is 3-5, and the quenching water temperature is 10-25 ° C.

[0041] Step 3, annealing treatment: heat the tube furnace to 800 ° C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, rewrap the Ti80 titanium alloy after two-phase zone heat treatment with titanium foil and place it in the middle of the furnace to ensure that the heating temperature is accurate and the heating is uniform. After 60 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and cool it in the air.

[0042] Figure 3 This is the microstructure diagram of the Ti80 titanium alloy after triple heat treatment in Comparative Example 1 of the present invention. Compared with Example 1, although the Ti80 titanium alloy undergoes the same near-β heat treatment and two-phase zone heat treatment, the annealing temperature of Comparative Example 1 is higher than the temperature range protected by the present patent application (500-550°C), and its phase composition is equiaxed α phase (9.6%) + lamellar α phase (37%) + β transformation structure, which is basically the same as Example 1, but the needle-shaped α phase in the β transformation structure grows significantly, and its average thickness is about 250nm, resulting in a significant decrease in its strength and plasticity.

[0043] In this comparative example, the room temperature tensile mechanical properties of the Ti80 titanium alloy after the triple heat treatment are as follows: yield strength is 839 MPa, tensile strength is 911 MPa, and total elongation at break is 15.6%.

[0044] Comparative Example 2 Step 1, near-β heat treatment: heat the tube furnace to 990°C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, place the Ti80 titanium alloy wrapped with titanium foil in the middle of the furnace, ensure that the heating temperature is accurate and the heating is uniform, and after 35 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and quench it in water. The quenching transfer time is 3~5s, and the quenching water temperature is 10~25°C.

[0045] Step 2, two-phase zone heat treatment: heat the tube furnace to 960 ° C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, rewrap the Ti80 titanium alloy after near-β heat treatment with titanium foil and place it in the middle of the furnace to ensure accurate heating temperature and uniform heating. After 60 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and place it in the air for cooling.

[0046] Figure 4This is a microstructure diagram of the Ti80 titanium alloy after double heat treatment in Comparative Example 2 of the present invention. The figure shows that the Ti80 titanium alloy presents a dual-state structural morphology after double heat treatment, and the structural parameters are equiaxed α phase (11.6%) + lamellar α phase (59.5%) + β transformation structure. Since the cooling method of Comparative Example 2 is air cooling instead of water cooling required by this patent, the lamellar α phase content increases significantly and the β transformation structure content decreases significantly, and the β transformation structure is mainly β phase, and the precipitated secondary α phase content is very low, so the strength is significantly reduced.

[0047] In this comparative example, the room temperature tensile mechanical properties of the Ti80 titanium alloy after the double heat treatment are as follows: yield strength is 809 MPa, tensile strength is 916 MPa, and total elongation at break is 15.8%.

[0048] Comparative Example 3 Step 1, near-β heat treatment: heat the tube furnace to 990°C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, place the Ti80 titanium alloy wrapped with titanium foil in the middle of the furnace, ensure that the heating temperature is accurate and the heating is uniform, and keep it warm for 35 minutes (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), turn off the heating program of the tube furnace, and cool the Ti80 titanium alloy to room temperature with the furnace.

[0049] Step 2, two-phase zone heat treatment: heat the tube furnace to 960 ° C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, wrap the Ti80 titanium alloy after near-β heat treatment with titanium foil and place it in the middle of the furnace to ensure accurate heating temperature and uniform heating. After 60 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and quench it in water. The quenching transfer time is 3~5s, and the quenching water temperature is 10~25 ° C.

[0050] Step 3, aging heat treatment: heat the tube furnace to 550 ° C, and after the furnace temperature stabilizes, introduce argon gas into the tube furnace, wrap the Ti80 titanium alloy after two-phase zone heat treatment with titanium foil and place it in the middle of the furnace to ensure that the heating temperature is accurate and the heating is uniform. After 60 minutes of insulation (the insulation time starts from the time the Ti80 titanium alloy is placed in the tube furnace), immediately take the Ti80 titanium alloy out of the tube furnace and cool it in the air.

[0051] Figure 5The microstructure diagram of the Ti80 titanium alloy after triple heat treatment in Comparative Example 3 of the present invention, the organizational parameters of Comparative Example 3 are lamellar α phase (23.2%) + β transformation organization, compared with Example 1, the equiaxial α phase in Comparative Example 3 almost disappears (content is about 1%), and the average thickness of the lamellar α phase is about 2.2μm. Since Comparative Example 3 is furnace cooled to room temperature after near-β heat treatment, which is not water-cooled as required by this patent, on the one hand, the equiaxial α phase formed at high temperature cannot be retained to room temperature, and on the other hand, the ɑ′ phase cannot be formed as the nucleation site of the lamellar α phase in the two-phase zone heat treatment. Therefore, the content of the equiaxial α phase and the lamellar α phase in Comparative Example 3 is significantly reduced, and the thickness of the lamellar α phase is significantly increased, resulting in a significant decrease in plasticity.

[0052] In this comparative example, the room temperature tensile mechanical properties of the Ti80 titanium alloy after the above triple heat treatment are as follows: yield strength is 854 MPa, tensile strength is 1000 MPa, and total elongation at break is 10.3%.

[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy, characterized in that: The method comprises the following steps: Step 1: Near-β heat treatment: keep the Ti80 titanium alloy at 985-990°C for 30-60 minutes, and quench with water to room temperature; Step 2, two-phase region heat treatment: the Ti80 titanium alloy after the near-β heat treatment is kept at 955-965° C. for 60-120 min, and water quenched to room temperature; Step 3: Aging heat treatment: The Ti80 titanium alloy after the two-phase zone heat treatment described in step 2 is kept at 500-550° C. for 60-120 min, and then air-cooled to room temperature.

2. A triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy according to claim 1, characterized in that: After the near-β heat treatment and water quenching in step 1, the microstructure of the Ti80 titanium alloy is equiaxed α phase + ɑ′ phase, wherein the content of the equiaxed α phase is 4-6%, and the average size of the equiaxed α phase is 6.5-7.5 μm.

3. A triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy according to claim 1, characterized in that: After the two-phase zone heat treatment and water quenching in step 2, the microstructure of the Ti80 titanium alloy is equiaxed α phase + lamellar α phase + ɑ′ phase, wherein the equiaxed α phase content is 8-12%, the average size of the equiaxed α phase is 7.5-8.5 μm, the lamellar α phase content is 25-30%, and the average thickness of the lamellar α phase is less than 1.3 μm.

4. A triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy according to claim 1, characterized in that: After the aging heat treatment in step 3 and air cooling, the microstructure of the Ti80 titanium alloy is equiaxed α phase + lamellar α phase + β transformation structure, wherein the equiaxed α phase content is 8-12%, the lamellar α phase content is 30-35%, the lamellar α phase has an average thickness of less than 1.5 μm, and a needle-shaped α phase with an average thickness of less than 120 nm is precipitated in the β transformation structure.

5. A triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy according to claim 1, characterized in that: During the water quenching process in step 1 and step 2, the quenching transfer time is 3 to 5 seconds and the quenching temperature is 10 to 25°C.

6. A triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy according to claim 1, characterized in that: The heat treatment is carried out in a resistance furnace in a vacuum or argon atmosphere, and during the heat treatment process, the Ti80 titanium alloy is placed in the middle of the resistance furnace.

7. A triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy according to claim 1, characterized in that: The heating method of the heat treatment is to heat and then sample.

8. A triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy according to claim 1, characterized in that: The Ti80 titanium alloy needs to be cleaned and degreased before heat treatment and wrapped with titanium foil, and the oxide scale on the surface needs to be removed after heat treatment.

9. A triple heat treatment method for synergistically improving the strength and plasticity of Ti80 titanium alloy according to claim 1, characterized in that: The constituent elements of the Ti80 titanium alloy are Al: 5.5-6.1wt%, Zr: 2.1-2.5wt%, Nb: 2.5-3.5wt%, Mo: 0.8-1.2wt%, and the rest are Ti and inevitable impurities, and the inevitable impurity elements include Si, C, N, H, O, and Fe, among which the content of Fe is less than 0.05wt%.

10. The Ti80 titanium alloy obtained by the triple heat treatment method according to any one of claims 1 to 9 is characterized in that: The microstructure of the Ti80 titanium alloy is equiaxed α phase + lamellar α phase + β transformation structure; the equiaxed α phase content is 8-12%, the lamellar α phase content is 30-35%, the lamellar α phase has an average thickness of less than 1.5 μm, and a needle-shaped α phase with an average thickness of less than 120 nm is precipitated in the β transformation structure.